(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Hyponatremia is a common electrolyte abnormality in patients with Stroke and is associated with increased morbidity and poor neurological outcomes. Syndrome of inappropriate antidiuretic hormone secretion (SIADH) and cerebral salt wasting syndrome (CSWS) are the major causes of hyponatremia in stroke patients. Early differentiation between these conditions is important because their management differs significantly. This study aimed to evaluate the occurrence of SIADH and CSWS among patients with stroke. Methodology: This hospital-based observational study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from January 2025 to December 2026. Fifty patients with clinically and radiologically confirmed stroke were included in the study. Detailed clinical evaluation, biochemical investigations, serum sodium levels, urine sodium, and assessment of volume status were performed. Data were analyzed using SPSS version 20.0. Chi-square test and Student’s t-test were used for statistical analysis, with p <0.05 considered statistically significant. Results: Hyponatremia was observed in 14% of stroke patients. Among patients with hyponatremia, 85.7% had SIADH and 14.3% had CSWS. Ischemic stroke constituted 80% of cases, and most patients had middle cerebral artery territory involvement. Severe hyponatremia (<125 mEq/L) was observed in 10% of patients. SIADH patients had normal volume status, whereas CSWS patients demonstrated hypovolemia and elevated BUN/creatinine ratio. Conclusion: Hyponatremia is a significant complication in stroke patients, with SIADH being the most common etiology. Early diagnosis and differentiation between SIADH and CSWS are essential for appropriate management and improved neurological outcomes.